Viral pandemics from smallpox to COVID-19 - Kavey, Rae-Ellen W.; Kavey, Allison 1977- (Routledge, 2021)
"Written by a public health practitioner and a medical historian, Viral Epidemics explores the terrifying world of viruses as the cause of all acute pandemics since 1900, including the COVID-19 pandemic. The book illuminates the critical dual roles of viral biology and increasing global interconnectedness that have resulted in an escalating pandemic spiral. Viral Epidemics is the only book that provides a complete historical narrative focused on viral epidemics. This comprehensive survey is designed for students and scholars in biology, epidemiology, public health, global history, and the history of medicine, as well as being of interest to the general reader"